Nutrition care as a health policy in the 21st century: a phenomenological study (2022)
Background: Addressing the high prevalence of disease-related malnutrition (DRM) requires political will. The aim of this study is to define DRM as a health public policy issue from the point of view of the stakeholders. Methods: We conducted a qualitative phenomenological study consisting of grey data search and individual semi-structured in-depth interviews with stakeholders (policy-makers, academics, and civil society organization representatives) from 17 Latin American countries. The analyzed themes reflected ideas repeatedly found across the interviews. Results: 26 respondents were interviewed (5 policy-makers, 18 academics, 3 civil society organizations representatives). The grey data research and interviews showed that Brazil and Costa Rica were the only countries in the Region that had developed a specific public health policy addressing DRM and nutrition care issues. The rest of the Latin American countries had a nutrition policy which neither addressed DRM specifically nor included nutrition care, with important heterogeneity existing in terms of national regulation of selected nutritional care categories. Stakeholder opinions allowed to identify heterogeneity in the understanding of the nature and causes of DRM, confusing DRM with malnutrition caused by food insecurity and lack of food availability. Policy in the field of clinical nutrition can be addresses from two approaches: interdisciplinarity and a human rights-based approach. Conclusion: DRM is an unaddressed problem by health policy. Due to internal and external factor related to the health systems DRM has not been able to become a public policy issue. The study highlights the need for the development of public policy in clinical nutrition aimed at improving access to nutrition care. © 2021 European Society for Clinical Nutrition and Metabolism